An Unstable Trinucleotide-Repeat Region on Chromosome 13 Implicated in Spinocerebellar Ataxia: A Common Expansion Locus - Vincent, John B. (2000)
Larger CAG/CTG trinucleotide-repeat tracts in individuals affected with schizophrenia (SCZ) and bipolar affective disorder (BPAD) in comparison with control individuals have previously been reported, implying a possible etiological role for trinucleotide repeats in these diseases. Two unstable CAG/CTG repeats, SEF2-1B and ERDA1, have recently been cloned, and studies indicate that the majority of individuals with large repeats as detected by repeat-expansion detection (RED) have large repeat alleles at these loci. These repeats do not show association of large alleles with either BPAD or SCZ. Using RED, we have identified a BPAD individual with a very large CAG/CTG repeat that is not due to expansion at SEF2-1B or ERDA1. From this individual's DNA, we have cloned a highly polymorphic trinucleotide repeat consisting of (CTA)n (CTG)n, which is very long (~1,800 bp) in this patient. The repeat region localizes to chromosome 13q21, within 1.2 cM of fragile site FRA13C. Repeat alleles in our sample were unstable in 13 (5.6%) of 231 meioses. Large alleles (>100 repeats) were observed in 14 (1.25%) of 1,120 patients with psychosis, borderline personality disorder, or juvenile-onset depression and in 5 (.7%) of 710 healthy controls. Very large alleles were also detected for Centre d'Etude Polymorphisme Humaine (CEPH) reference family 1334. This triplet expansion has recently been reported to be the cause of spinocerebellar ataxia type 8 (SCA8); however, none of our large alleles above the disease threshold occurred in individuals either affected by SCA or with known family history of SCA. The high frequency of large alleles at this locus is inconsistent with the much rarer occurrence of SCA8. Thus, it seems unlikely that expansion alone causes SCA8; other genetic mechanisms may be necessary to explain SCA8 etiology.